A Randomized Trial of Expanding Choice Sets to Motivate Advance Directive Completion. (July 2017) - Courtright, Katherine R.; Madden, Vanessa; Gabler, Nicole B.; Cooney, Elizabeth; Kim, Jennifer; Herbst, Nicole; Burgoon, Lauren; Whealdon, Jennifer; Dember, Laura M.; Halpern, Scott D.
Background. Evidence suggests that advance directives may improve end-of-life care among seriously ill patients, but improving completion rates remains a challenge.Objective. This study tested the influence of increasing the number of options for completing an advance directive among seriously ill patients.Methodology. Outpatients ( N = 316) receiving hemodialysis across 15 dialysis centers in the Philadelphia region between July 2014 and July 2015 were randomized to receive either the option to complete a brief advance directive form or expanded options including a brief, expanded, or comprehensive form. Patients in both groups could decline to complete an advance directive or take their selected version home. The primary outcome was a returned, completed advance directive. Secondary outcomes included whether patients wanted to complete an advance directive, decision satisfaction, quality of life at 3 months, and patient factors associated with advance directive completion.Results. Although offering more advance directive options was not significantly associated with increased rates of completion (13.1% in the standard group v. 12.2% in the expanded group, P = 0.80), it did significantly increase the proportion of patients who wanted to complete an advance directive and took one home (71.9% in standard v. 85.3% in expanded, P = 0.004). There was no difference in satisfaction ( P = 0.65) or change in quality of life between groups ( P = 0.63). A higher baseline quality of life was independently associated with advance directive completion ( P = 0.006).Conclusions and Relevance. These results suggest that although an expanded choice set may initially nudge patients toward completing advance directives without restricting choice, increasing actual completion requires additional interventions that overcome downstream barriers.